2004
DOI: 10.1002/j.1939-4640.2004.tb02843.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the p63 and Notch Signaling Systems in Rat Testes During Postnatal Development: Comparison With Their Expression Levels in the Epididymis and Vas Deferens

Abstract: : The role of tubular structures that contribute to the passage of spermatozoa is not solely passive; these structures actively contribute to their own functions, although these tubules and ducts are contiguous and collaborate in the development of the male gamete along their lengths. The testis has the specific function to generate spermatozoa and spermatozoa undergo numerous changes as they pass through the epididymis. A member of the p53 family of genes, p63, is highly expressed in the basal layers of epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
2
28
0
1
Order By: Relevance
“…3E, C, J and N) which persisted into adulthood (Fig. 2); these findings are consistent with those reported by Hayashi et al (2004). In addition to the continuous layer of basal cells in the proximal and distal vas deferens, CK-HMW/p63 immunopositive cells also appeared in the proximal cauda between days 10 and 18 but they did not form a continuous layer (Fig.…”
Section: Ontogeny Of Basal Cell Development In the Vas Deferens (Immusupporting
confidence: 89%
“…3E, C, J and N) which persisted into adulthood (Fig. 2); these findings are consistent with those reported by Hayashi et al (2004). In addition to the continuous layer of basal cells in the proximal and distal vas deferens, CK-HMW/p63 immunopositive cells also appeared in the proximal cauda between days 10 and 18 but they did not form a continuous layer (Fig.…”
Section: Ontogeny Of Basal Cell Development In the Vas Deferens (Immusupporting
confidence: 89%
“…p63 exists as two isoforms, ⌬Np63 and TAp63, that are generated by alternate promoters. ⌬Np63 is the isoform that is expressed in basal cells in genital tract epithelia (13,36) and has been shown to be necessary for the development of epithelial tissues (42). Consistent with these findings, real-time PCR analysis demonstrated that ⌬Np63, not TAp63, is the isoform that is expressed by the expanded pool of basal cells in (Fig.…”
Section: Expansion Of Basal Cells In Tumors Insupporting
confidence: 68%
“…Pseudostratified epithelia of the genitourinary tract, including the epididymal tubules, vesicular glands, vas deferens, prostate, and urothelium, are lined by a population of p63-expressing basal cells (13,36). While the functions of basal cells are incompletely characterized for most tissues, detailed studies of the prostate have shown that basal cells act as progenitor cells that are necessary for prostatic development (10).…”
Section: Expansion Of Basal Cells In Tumors Inmentioning
confidence: 99%
“…8 KLF4 is highly expressed by the whole epithelium of the epididymis of the mouse. 9 Notch1 mRNA is in all epididymal regions, without cellular identity; 10 Notch1 is only detectable by in situ hybridisation in hyperplastic epididymal epithelial cells of constitutively active Notch1-transgenic mice. 11 These embryonic stem cell factors may have other functions, such as cellular differentiation, in the adult epididymis.…”
Section: Cells-of-origin Of Epididymal Tumours Epididymal Stem Cellsmentioning
confidence: 98%